Definitive Journeys. Mes années Cuba by Eduardo Manet (Anclajes, 2023)
Mes années Cuba, an autobiographical text by the Cuban Eduardo Manet, includes his vital experiences and reveals his perception of the political, social and cultural changes that take place in Cuba with the triumph of the Revolution and with the progressive rapprochement towards the Soviet Union. The sudden change of direction of the revolutionary project towards communism, as well as the trips he made to various socialist countries from Eastern Europe, will lead him to convert his ideological convictions and even make decisions that will permanently change his future.
Keywords: Autobiography; Cuba; Soviet Union; Cultural relations